2020
DOI: 10.1126/science.aba5244
|View full text |Cite
|
Sign up to set email alerts
|

Marine heat waves threaten kelp forests

Abstract: The user has requested enhancement of the downloaded file.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 10 publications
1
49
0
Order By: Relevance
“…Our results, like others around the world, indicate that temperate kelp forest ecosystems appear especially vulnerable to marine heatwaves because of the pronounced effects on kelps as foundation species (sensu Dayton, 1972), which serve as major sources of primary production and physical habitat structure (e.g., Arafeh-Dalmau et al, 2020;Filbee-Dexter, Feehan, & Scheibling, 2016;Filbee-Dexter, Wernberg, Fredriksen, Norderhaug, & Pedersen, 2018;Martínez et al, 2018;Rogers-Bennett & Catton, 2019;Smale & Wernberg, 2013;Tanaka et al, 2012;Thomsen et al, 2019;Vergés et al, 2016;Wernberg et al, 2010Wernberg et al, , 2011Wernberg et al, , 2012Wernberg et al, , 2016. We found that region-wide declines in abundance of canopy-forming kelps were strongly associated with the recent marine heatwave.…”
Section: Geographic Range and Ecosystem Structure Shiftssupporting
confidence: 77%
“…Our results, like others around the world, indicate that temperate kelp forest ecosystems appear especially vulnerable to marine heatwaves because of the pronounced effects on kelps as foundation species (sensu Dayton, 1972), which serve as major sources of primary production and physical habitat structure (e.g., Arafeh-Dalmau et al, 2020;Filbee-Dexter, Feehan, & Scheibling, 2016;Filbee-Dexter, Wernberg, Fredriksen, Norderhaug, & Pedersen, 2018;Martínez et al, 2018;Rogers-Bennett & Catton, 2019;Smale & Wernberg, 2013;Tanaka et al, 2012;Thomsen et al, 2019;Vergés et al, 2016;Wernberg et al, 2010Wernberg et al, , 2011Wernberg et al, , 2012Wernberg et al, , 2016. We found that region-wide declines in abundance of canopy-forming kelps were strongly associated with the recent marine heatwave.…”
Section: Geographic Range and Ecosystem Structure Shiftssupporting
confidence: 77%
“…The trend of global warming is one of the most important climate change changes of recent decades, which researchers provided on a regional and planetary scale [1][2][3][4] . Climate change and global warming, and its consequences for life and the process of development in human societies, have become the greatest global issue.…”
Section: Introductionmentioning
confidence: 99%
“…Regional studies have shown the negative effect of warming on brown macroalgae (Sansón et al 2013). In addition to rising temperatures, the role of extreme hightemperature events (marine heatwaves) also has a negative impact on fucoid populations (Vergés et al 2014;Arafeh-Dalmau et al 2020). As the magnitude and frequency of extreme events are expected to increase under climate change (Gaines and Denny 1993;Coumou and Rahmstorf 2012;Frölicher and Laufkötter 2018), this should be taken into consideration in future experiments testing their effects on canopy-forming algae in Madeira.…”
Section: Possible Causes and Impactsmentioning
confidence: 99%